Implementasi Algoritme Grain dan SHA-3 untuk Data Lokasi - Indriyana Liliasari Rahma Yusvi; Ari Kusyanti; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Ambulan Online is a mobile-based application for tracking the location of the ambulance which is expected to increase response time by getting the nearest ambulance position. In the process of using it, there is data transmission from the application to the server. The data is sent in plain text which is a weakness for patient data security. Even though there are regulations regarding the confidentiality of medical records which are regulated in the Regulation of the Minister of Health Number 269 of 2008 concerning Medical Records. Based on this, the author will implement the Grain Algorithm and SHA-3 as encryption on patient data, location data and patient information. After that, conduct testing using a test vector to ensure the Grain Algorithm and SHA-3 used matching with the creator's property. To test the travel time of data on the entire system, researcher using data processing test by input 30 times data in that experiment. In this test, the average data processing time from the time the application user delivers the patient to the patient data entry is 5.6 seconds. Third is integrity test are carried out by checking the results of hashing data on SHA-3. Finally, researcher testing the key generation scheme to ensure key generation can function properly. The conclusion is that there is a difference in travel time after the Grain and SHA-3 Algorithm is implemented, but the patient data integrity aspect is met with the results of the integrity testing that has been carried out.